2024
DOI: 10.1007/s00296-024-05579-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characteristics of early-onset and delayed-onset lupus nephritis patients: A single-center retrospective study

Joanna Kosałka-Węgiel,
Radosław Dziedzic,
Andżelika Siwiec-Koźlik
et al.

Abstract: Background Lupus nephritis (LN) manifests systemic lupus erythematosus (SLE) and is characterized by various clinical and laboratory features. This study aimed to comprehensively evaluate the characteristics of LN patients according to the time of LN diagnosis: early-onset (LN diagnosed within one year from SLE diagnosis) vs. delayed-onset (LN diagnosed more than one year after SLE diagnosis). Methods We conducted a retrospective analysis of medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Moreover, a Polish study reported a lower frequency of proteinuria (22.5%) [ 20 ]. Renal biopsy was done in 13 patients and the predominant histopathological pattern was Class IV (46.15%), similar to other studies done in Nigeria, Brazil, Poland, and Egypt [ 10 , 22 , 30 , 31 ]. However, a South African study reported Class V while a Sudanese study reported Class III as their predominant renal pathologic features [ 15 , 32 ].…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, a Polish study reported a lower frequency of proteinuria (22.5%) [ 20 ]. Renal biopsy was done in 13 patients and the predominant histopathological pattern was Class IV (46.15%), similar to other studies done in Nigeria, Brazil, Poland, and Egypt [ 10 , 22 , 30 , 31 ]. However, a South African study reported Class V while a Sudanese study reported Class III as their predominant renal pathologic features [ 15 , 32 ].…”
Section: Discussionsupporting
confidence: 75%